MANAGEMENT OF COLON AND CLOACAL PROLAPSE IN TURTLE: A REPORT OF FIVE CLINICAL CASES - Jain, Rajkumar; Jain, Reshma; Verma, SK (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Turtles are reptile of the order Chelonii or Testudines characterised by a special bony or cartilaginous shell developed from their ribs that act as a shield.Cloaca is a cylindrical organ that opens to the outside of the turtle’s body. In chelonians, the colon, the urinary bladder, the penis of males, the oviducts and shell glands of females, and the cloaca itself may prolapse, that is, slip from their normal position, move down the cloaca and pass out through the anal vent. It receives waste product from the large intestine, bladder and sperm(male) or egg (Sandy and Herpetologist, 2010 and siegmud, 2008).